The occurrence of Cryptosporidium oocysts and physical assessment of selected lakes in Kuantan, Pahang - Mat Yusof, Afzan; Mohammad, Mardhiah; Abdullah, Qamarul Iqmal; Soffian, Sharmeen Nellisa; Hisamuddin, Nur Hazirah; Hashim, Najat; Abdul Wahab, Ridhwan (2015)
Parasitic infection is one of major public health problems especially in developing countries. Cryptosporidium is one of the common human parasites that cause waterborne disease outbreak in industrialized countries. In this present study, we aimed to determine the occurrence of Cryptosporidium and to determine whether a statistical association existed between the occurrences and physical parameters in water samples from selected recreational lakes in Kuantan, Pahang, Malaysia. Samples were collected from three stations of Lake TG and Lake TB for three consecutive months, from November 2014 to January 2015. The samples were processed to detect the presence of the waterborne protozoa using flat-bed membrane filtration technique. Between the two lakes, the occurrence of Cryptosporidium was higher in Lake TB (0.66 oocysts/L) as compared to Lake TG (0.53 oocysts/L). For monthly occurrence trend for both lakes, the number of Cryptosporidium oocysts present was highest in November, followed by January, and lastly December. In Lake TG, the occurrence of these protozoa was 0.27 oocysts/L during November, 0.06 oocysts/L during December, and 0.20 oocysts/L during January while in lake TB, the occurrence of Cryptosporidium was 0.37 oocysts/L during November, 0.06 oocysts/L during December, and 0.23 oocysts/L during January. All the physical parameters did not show any significant correlation with the protozoa based on Pearson correlation analysis where p (probability level) > 0.05. Therefore, these physical parameters are not suitable for the indicator of the presence of these parasite oocysts in both lakes. Based on the results, it is clearly shown that there is a need to implement the detection of waterborne protozoa and physico-chemical analysis in Malaysia. In, addition, the analysis of heavy metals (copper, mercury, chromium, and zinc) is also recommended for this type of study. Hence, molecular characterization and viability status of Cryptosporidium should be applied to identify species and genotypes for better understanding of the epidemiology of this waterborne parasite.